Kandungan Mikroplastik pada Saluran Pencernaan Ikan Katombo (Rastrellinger kanagurta) dari Teluk Palu dan Pemanfaatannya sebagai Media Pembelajaran - Moh Dhuhri Surya Wirawan; Fatmah Dhafir; I Made Budiarsa; Gamar Binti Non Shamdas (Media Eksakta, 2021)
Microplastics are plastic pieces smaller than 5 mm. This study aims to describe the mikroplastic content in the digestive tract of Mackerel fish (Rastrellinger kanagurta) arising from the Palu Bay, and its use as a learning media. Samples in this research are some 10 % of the catch fishermen. Technique data collection was carried out using a technique analysis of the stomach contents. Result of the research are that abundance highest on station I with 2,2 particles, station II 0,83 particles, and in stations III 1,5 particles.  Validated of video by team validator obtained to 76.86 %, video can be described as learning so that it can be used as a Learning media.